Effect of Pre-Sowing Treatments on Growth Attributes of Sapindus mukorossi Gaertn - Attri, Varun (Indian Forester, 2023)
The present study was aimed to evaluate the various pre-sowing treatments on seed germination, its subsequent seedling growth behaviour and biomass of Sapindus mukorossii. Seeds were graded in to three categories viz. small, medium and large and treated with five pre- sowing treatments viz. T1 (control), T2 (cold water soaking for 72 hours), T3 (keeping in cow dung for 7 days), T4 (immersion in conc. H2SO4 for 20 min followed by rinsing under running tap water), T5 (immersion of seeds in hot water at 80Â°C followed by 24 hour soaking). It was found that the large seed (L3) exhibit maximum growth 3 and seedling biomass at different time interval. Among treatments, T4 was found to be best and produced higher germination per cent and seedling growth characteristics viz. shoot and root length, collar diameter, seedling height, number of lateral roots and seedling biomass viz. shoot and root dry weight and total dry weight production at different time interval. Among interactions, L3 when treated with T4 excelled over other seed size and pre-sowing treatment combinations.